Предмет:
МатематикаАвтор:
аноним((2y - 1)/((y^2) + 2y + 4) + (9y + 6)/((y^3) - 8) + 1/(y - 2)) * (((y^2) - 4)/18) =1. Выполним все действия с первой скобкой. Т.к. y^3 - 8 = (y - 2)(y^2 + 2y +4), то1) (2y-1)/(y^2) = (2y^2 - 5y + 2)/(y - 2)(y^2 + 2y +4)2) 1/(y-2) = (y^2 + 2y +4)/(y - 2)(y^2 + 2y +4)3) 2y^2 - 5y + 2 + 9y + 6 + y^2 + 2y +4 = 3y^2 + 6y + 12 = 3 * (y^2 + 2y + 4)4) 3 * (y^2 + 2y + 4)/(y - 2)(y^2 + 2y +4) = 3/(y - 2)2. Упростим вторую скобку:1) (y^2) - 4 = (y - 2)(y + 2)3. Перемножим обе скобки: 1) 3/(y - 2) : (y - 2)(y + 2)/18 = (y + 2)/6Ответ: (y + 2)/6
Автор:
solisДобавить свой ответ
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть